THE USE OF MULTIMEDIA INTERACTIVE DEVICE OF EPRESENTER IS IN TEACHING OF MATHEMATICS (Journal of Information Technologies in Education (ITE), 2011)
The use of multimedia interactive device of eRresenter is examined in teaching of mathematics as will build on for studies and presentation.
Keywords: information technologies; interactive complexes; interactive device; Interactiveness